Patterns of acute poisoning in children: an epidemiological study from a tertiary care centre - Dr Chapay Soren; Dr Kuldip Paike (Pediatric Review: International Journal of Pediatric Research, 2015)
Objectives: Acute poisoning in children is an important public health problem worldwide. It is responsible for 0.33% to 7.6% of total admissions in pediatric wards at various hospitals across India. The aim of this study was to assess the pattern of acute poisoning among children (birth to 12 years).Methods: We retrospectively reviewed the hospital records of all children from birth to 12 years of age with definite history of poisoning during the 3 years period from October 2012 to September 2015.Results: Of the 203 patients admitted with acute poisoning during the study period, majority (81%) were between 1 to 6 years of age. Male to female ratio was 1.36:1. 68.96% were from rural areas and 31.04% from urban areas. Household products (50.24%), drugs (28.07%), and pesticides and rodenticides (13.30%) were the most frequently implicated agents. Kerosene was major household product implicated. Among drugs, analgesics and antipyretics are commonly implicated. The nature of poisoning was accidental in 98.03% cases. Systems involved in the order of frequency were gastrointestinal, cardiorespiratory, neurological, and others. 89% were discharged after treatment, 5.91% went absconding, 3.44% left against medical advice, and 0.98% expired. Both children who died were 3 years of age and had organophosphorous poisoning.Conclusion: The pattern of acute poisoning in children noted at our centre was not very different from that observed in other hospital based studies from India. There is a strong need for preventive campaign to reduce the occurrence acute poisoning in children.